An envision of conceptosphere of emotions and feelings by paralinguistic phraseologisms (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the research of means of emotions and feelings in the language, i.e. love and sympathy; the author investigates the peculiarities of semantic organization of paralinguistic phraseological units, explains the nature of realization of predetermined connotative meanings in their semantics, while emphasizing the peculiarities of their increased emotionality.
Keywords: emotion; feeling; emotional semantics; paralinguistical (mimical) phraseologism